2022
DOI: 10.1096/fj.202200118rr
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel targets in adipose tissue involved in non‐alcoholic fatty liver disease progression

Abstract: Obesity is a major risk factor for the development of Nonalcoholic fatty liver disease (NAFLD). We hypothesize that a dysfunctional subcutaneous white adipose tissue (scWAT) may lead to an accumulation of ectopic fat in the liver. Our aim was to investigate the molecular mechanisms involved in the causative role of scWAT in NALFD progression. We performed a RNA‐sequencing analysis in a discovery cohort (n = 45) to identify genes in scWAT correlated with fatty liver index, a qualitative marker of liver steatosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…SOCS3 plays a role in liver insulin resistance and increased inflammation that accelerates simple steatosis [ 134 ]. SOCS3 expression in adipose tissue is parallel to the degree of steatosis [ 135 ], SOCS3 , is regulated by microRNA-650, and controls JAK/STAT3 signaling, posing a risk factor for MASLD and hepatocellular carcinoma [ 136 ]. SOCS3 negatively regulates insulin and leptin signaling [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOCS3 plays a role in liver insulin resistance and increased inflammation that accelerates simple steatosis [ 134 ]. SOCS3 expression in adipose tissue is parallel to the degree of steatosis [ 135 ], SOCS3 , is regulated by microRNA-650, and controls JAK/STAT3 signaling, posing a risk factor for MASLD and hepatocellular carcinoma [ 136 ]. SOCS3 negatively regulates insulin and leptin signaling [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Lopez-Yus et al reported that the expression of DUSP1 paralleled the degree of steatosis, and DUSP1 could be a key player in the progression of NAFLD. 27 JUNB, a member of the Fos/Jun family, is a key component of activator protein transcription factors and a major target element of mitotic activation and transmission pathways. 28 Previous studies have found that JUNB negatively regulated cell proliferation and Ras-mediated malignant transformation while also participating in proapoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Lopez-Yus et al reported that the expression of DUSP1 paralleled the degree of steatosis, and DUSP1 could be a key player in the progression of NAFLD. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Changes in leptin signaling in patients with NAFLD are related to the pathophysiology of this disease; thus, the association of polymorphisms in the leptin receptor gene with NAFLD has been described [ 257 ]. In addition, mesenchymal stem cell-derived adipocytes from obese patients at different stages of NAFLD have impaired adipogenesis as liver steatosis augmented, showing a differential expression pattern in SOCS3, comparable to steatosis degree [ 258 ]. Different data in animals and humans show a relationship of certain miRNAs with hepatic metabolic homeostasis and leptin signaling.…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%